ORIGIN OF TOURMALINE GRANITOIDS OF MEGHRI PLUTON'S VANK INTRUSIVE MASSIVE (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
In the Vank granitoids turmalin is spread unevenly regardless of magmatic and tectonic cracks. The three types of turmaline: magmatic (porphyric inclusions in the granitoids), pneumatolytic (radial-rays aggregates in the andesits at the top of Vank's massive) and hydrothermal (quartz-turmaline veins in the exocontact gabbros and monzonite), are genetically associated with magmatic and post magmatic processes of the boron enriched Vank's intrusive.
Keywords: tourmaline granitoids; borates; magmatic genesis of tourmaline